Calibrated Enhanced-Resolution Passive Microwave Daily EASE-Grid 2.0 Brightness Temperatures Derived from Level 1C FCDR - Brodzik, Mary; Long, David; Hardman, Molly (National Snow and Ice Data Center, Boulder, CO, USA, 2021)
This data set (nsidc0763) is a prototype for a major re-processing effort of the multi-sensor Level 3 Earth Science Data Record (ESDR) known as Calibrated Enhanced Resolution Brightness Temperature (CETB, https://nsidc.org/data/nsidc-0630/versions/1). This prototype for CETBv2 data uses input sensor data from the Level 1C Fundamental Climate Data Record (FCDR), which employs an improved intercalibration method based on the Global Precipitation Mission (GPM) Microwave Imager (GPM) sensor record. Cross-calibrated measurements from SSMIS instruments on DMSP-F16, -F17, -F18, and the AMSR2 instrument on GCOMW1 are included in the prototype data. Minor updates to the CETBv1 Climate-Forecast (CF) compliant file-level metadata are included. Brodzik et al. (2023) contains further details on CETBv2 processing. The prototype filename convention follows the naming convention of CETBv1 files (Brodzik and Long, 2018), which will be replaced with a different convention in the official CETBv2 release, as described in Brodzik et al. (2023). Data contents of the prototype data set do not significantly differ from the contents of CETBv2. The prototype data set has been produced as a temporary means to make the new sensor inter-calibration method and the additional sensor data from AMSR2 available to users, in advance of the complete repocessing as CETBv2 at the National Snow and Ice Data Center (NSIDC) Distributed Active Archive Center (DAAC). The NSIDC DAAC anticipates that the complete CETBv2 data set (including complete sensor data records from 6 SSM/I, 4 SSMIS, AMSR-E and AMSR2 sensors) will be publicly available in 2024, at which time this prototype will be discontinued. Data are gridded to three EASE-Grid 2.0 projections (North Azimuthal, South Azimuthal, and Cylindrical) and include enhanced-resolution imagery, as well as coarse-resolution, averaged imagery. The prototype data have only been produced for limited periods for sensors that are currently operational: Special Sensor Microwave Imager/Sounder (SSMIS) on DMSP ...